2016
DOI: 10.1007/s10265-016-0864-6
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and ecological investigations on the wild populations of Glycyrrhiza L. taxa distributed in the East Mediterranean Area of Turkey

Abstract: This paper covers studies on the molecular and ecological aspects of G. glabra var. glandulifera, G. flavescens ssp. flavescens and G. echinata collected from Hatay (Turkey); with the aim to better understand their genetic variation and ecological requirements for possible conservation programs. The material including total genomic DNA was extracted by the CTAB, and for PCR reaction, a total of 14 SSR primers developed for Medicago truncatula were used. PCR amplifications were performed in a Multigen Thermal C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 36 publications
3
11
0
2
Order By: Relevance
“…Within Glycyrrhiza s.l., we recognized four main clades (Figure 1) that are consistent with earlier studies having more limited sampling of the genus (Erayman et al, 2014;Çetin, 2015;Altay et al, 2016). Clade I includes Glycyrrhizopsis flavescens and Glycyrrhiza asymmetrica (Figure 1) and is sister to Glycyrrhiza sensu Meng.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Within Glycyrrhiza s.l., we recognized four main clades (Figure 1) that are consistent with earlier studies having more limited sampling of the genus (Erayman et al, 2014;Çetin, 2015;Altay et al, 2016). Clade I includes Glycyrrhizopsis flavescens and Glycyrrhiza asymmetrica (Figure 1) and is sister to Glycyrrhiza sensu Meng.…”
Section: Discussionsupporting
confidence: 87%
“…was sister to the rest of Glycyrrhiza s.l. (Erayman et al, 2014;Çetin, 2015;Altay et al, 2016). However, none of these prior studies showed Glycyrrhiza to be monophyletic, and all suffered from undersampling (i.e., a maximum of seven species) and, therefore, did not represent strong molecular evidence.…”
Section: Introductionmentioning
confidence: 99%
“…Within Glycyrrhiza s.l., we recognized four main clades (Figure 1) that are consistent with earlier studies having more limited sampling of the genus [16,27,28]. Clade I includes Glycyrrhizopsis flavescens and Glycyrrhiza asymmetrica (Figure 1) and is sister to Glycyrrhiza sensu Meng.…”
Section: Phylogenetic Relationships Of Glycyrrhiza Slsupporting
confidence: 87%
“…was sister to the rest of Glycyrrhiza s.l. [17,27,28]. However, none of these prior studies showed Glycyrrhiza to be monophyletic, and all suffered from www.videleaf.com under-sampling (i.e, a maximum of seven species) and, therefore, did not represent strong molecular evidence.…”
Section: Introductionmentioning
confidence: 99%
“…Bu çalışmada incelenen Geranium türleri 2013-2015 yılları arasında Hatay il sınırları içindeki 24 farklı alandan toplanmıştır. Türkiye'nin Doğu Akdeniz Bölgesi'nde bulunan Hatay ili (35°48′-37°00′ K / 35°46′-36°41′ D) tipik Akdeniz iklimine sahip olup, yıllık ortalama sıcaklık 18.1 °C ve ortalama yağış 1.078 mm'dir (Altay, Karahan, Öztürk, Hakeem, İlhan, & Erayman, 2016). Doğal habitatlarından toplanan bitki örnekleri Türkiye Florası'na göre (Davis, 1967) Mikroskopta yapılan morfolojik incelemeler sonunda polenlerin polar çapı, ekvatoral çapı, ekzin ve intin kalınlığı, kolpus ve porus uzunluğu, kolpus ve porus açıklığı ölçülmüştür.…”
Section: Materyal Ve Metotunclassified